2007
DOI: 10.1007/s11104-007-9420-4
|View full text |Cite
|
Sign up to set email alerts
|

The upscaling of transpiration from individual trees to areal transpiration in tree belts

Abstract: Sap flow measurements have long been used to measure transpiration in individual trees and there exist some well established methods for upscaling individual tree volumetric transpiration to areal transpiration in plantation and forest plots. However, where edge effects are significant, such as in tree belts, the area the volumetric transpiration is to be projected upon is unknown. This paper provides a methodology for estimating the area that a tree belt hydrologically occupies by using either measurements of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Numerous studies dealing with tree water use and transpiration have based their scaling from individual trees to stands around the relation between sapwood area and tree diameter (e.g. Vertessy et al 1995;Meinzer et al 2005;Crosbie et al 2008;Wang et al 2010;Jung et al 2011) and such models require determination of D S as accurately as possible. Small measurement errors can lead to large over-or under-estimation of actual water use Köstner et al 1998;Bovard et al 2005;Bieker and Rust 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies dealing with tree water use and transpiration have based their scaling from individual trees to stands around the relation between sapwood area and tree diameter (e.g. Vertessy et al 1995;Meinzer et al 2005;Crosbie et al 2008;Wang et al 2010;Jung et al 2011) and such models require determination of D S as accurately as possible. Small measurement errors can lead to large over-or under-estimation of actual water use Köstner et al 1998;Bovard et al 2005;Bieker and Rust 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Foliage leaves are the principal photosynthetic organs of most plants (Gates et al, 1966;Wright et al, 2004;Crosbie et al, 2007). Variations in leaf initiation and subsequent growth result in different leaf shapes and sizes (Byrne et al, 2001).…”
mentioning
confidence: 99%
“…Tree transpiration tends to have more constant rates in the middle of the day (flat top) than pasture evapotranspiration (Crosbie et al, 2007). However, in tree belts measured by Crosbie et al (2007), they reported a steep increase/decrease in the beginning/end of the day compared to the pasture. Conversely, our results show a smooth increase/decrease, similar to the pasture (Figure 9c, d).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, our results show a smooth increase/decrease, similar to the pasture (Figure 9c, d). Differently from Crosbie et al (2007), who reported only 1 day of measurements, we presented averages by season, which might have smoothed out the results; additionally, the edge effect is more significant in tree belts, where trees are more susceptible to the incidence of solar radiation, while in the plantation there is more competition for solar energy (Ellis et al, 2005). Note: ET wb is estimated from Equation (4).…”
Section: Evapotranspiration and Transpiration Ratesmentioning
confidence: 99%